2021
DOI: 10.1136/annrheumdis-2020-219262
|View full text |Cite
|
Sign up to set email alerts
|

TNF is a homoeostatic regulator of distinct epigenetically primed human osteoclast precursors

Abstract: ObjectivesCirculating myeloid precursors are responsible for post-natal osteoclast (OC) differentiation and skeletal health, although the exact human precursors have not been defined. Enhanced osteoclastogenesis contributes to joint destruction in rheumatoid arthritis (RA) and tumour necrosis factor (TNF) is a well-known pro-osteoclastogenic factor. Herein, we investigated the interplay between receptor activator of nuclear factor kappa-Β ligand (RANK-L), indispensable for fusion of myeloid precursors and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…Of note, also human terminally differentiated peripheral cDCs have a robust capacity to differentiate into bone resorbing OCs, suggesting that also in humans DCs possibly contribute to OCs. The recently described CD11c + myeloid cells with osteoclastogenic potential are possibly overlapping with our CD1c + cDC population, highlighting the potential of DC like cells as OC precursors 47…”
Section: Discussionsupporting
confidence: 71%
“…Of note, also human terminally differentiated peripheral cDCs have a robust capacity to differentiate into bone resorbing OCs, suggesting that also in humans DCs possibly contribute to OCs. The recently described CD11c + myeloid cells with osteoclastogenic potential are possibly overlapping with our CD1c + cDC population, highlighting the potential of DC like cells as OC precursors 47…”
Section: Discussionsupporting
confidence: 71%
“…In humans, three subpopulations of MN-derived OCPs have been described: classical MNs (CD14 + CD16 − ), 14 intermediate MNs (CD14 high CD16 + ), 129 , 130 and a circulating myeloid population (CD14 − CD16 − CD11c + ). 131 …”
Section: Part II Diversity Of Osteoclast Precursors In Chronic Inflam...mentioning
confidence: 99%
“…The circulating CD14 − CD16 − CD11c + myeloid population rapidly differentiated into more numerous and larger OCs than those differentiated from CD14 + OCPs. 131 It was reported that 56% of patients with moderate-to-severe active RA were unresponsive to TNF-α treatment because TNF-α inhibited osteoclastic differentiation of classical or intermediate MN OCPs (CD14 + ) but not myeloid OCPs (CD11c + ). 131 …”
Section: Part II Diversity Of Osteoclast Precursors In Chronic Inflam...mentioning
confidence: 99%
See 1 more Smart Citation
“…This method aimed to easily differentiate a large number of OCs from human peripheral blood CD14 + monocytes in vitro, typically in 1 week. Firstly, CD14 + monocytes were enriched from PBMCs and primed with M-CSF overnight to upregulate RANK, as previously reported 15 . Following monocyte priming, to determine the optimum concentration of RANKL for OC differentiation and maturation, RANKL concentrations of 1 ng/mL, 25 ng/mL, 50 ng/mL, and 100 ng/mL, along with 25ng/mL M-CSF, were used.…”
Section: Oc Generation From Cd14 + Monocytesmentioning
confidence: 99%